Effect of vimentin on cell migration in collagen-coated microchannels: A mimetic physiological confined environment - Zhou, Zhiru; Cui, Feiyun; Wen, Qi; Susan Zhou, H. (Biomicrofluidics, 2021)
Cancer cell migration through tissue pores and tracks into the bloodstream is a critical biological step for cancer metastasis. Although in vivo studies have shown that expression of vimentin can induce invasive cell lines, its role in cell cytoskeleton reorganization and cell motility under in vitro physical confinement remains unknown. Here, a microfluidic device with cell culture chamber and collagen-coated microchannels was developed as an in vitro model for physiological confinement environments. Using this microchannel assay, we demonstrated that the knockdown of vimentin decreases 3T3 fibroblast cell directional migration speed in confined microchannels. Additionally, as cells form dynamic membranes that define the leading edge of motile cells, different leading edge morphologies of 3T3 fibroblast and 3T3 vimentin knockdown cells were observed. The leading edge morphology change under confinement can be explained by the effect of vimentin on cytoskeletal organization and focal adhesion. The microfluidic device integrated with a time-lapse microscope provided a new approach to study the effect of vimentin on cell adhesion, migration, and invasiveness.